Viewing pre-60S maturation at a minute's timescale. Issue 6 (27th December 2017) - Zisser, Gertrude; Ohmayer, Uli; Mauerhofer, Christina; Mitterer, Valentin; Klein, Isabella; Rechberger, Gerald N; Wolinski, Heimo; Prattes, Michael; Pertschy, Brigitte; Milkereit, Philipp; Bergler, Helmut
Abstract: The formation of ribosomal subunits is a highly dynamic process that is initiated in the nucleus and involves more than 200 trans -acting factors, some of which accompany the pre-ribosomes into the cytoplasm and have to be recycled into the nucleus. The inhibitor diazaborine prevents cytoplasmic release and recycling of shuttling pre-60S maturation factors by inhibiting the AAA-ATPase Drg1. The failure to recycle these proteins results in their depletion in the nucleolus and halts the pathway at an early maturation step. Here, we made use of the fast onset of inhibition by diazaborine to chase the maturation path in real-time from 27SA2 pre-rRNA containing pre-ribosomes localized in the nucleolus up to nearly mature 60S subunits shortly after their export into the cytoplasm. This allows for the first time to put protein assembly and disassembly reactions as well as pre-rRNA processing into a chronological context unraveling temporal and functional linkages during ribosome maturation.